Valuing risk reductions: Testing for range biases in payment card and random card sorting methods - Ian J. Bateman; Judith Covey; Graham Loomes (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2005)
Concerns have been raised that the payment card (PC) format widely used in contingent valuation surveys of health treatments and risk reductions is subject to range bias. In response recent surveys have adopted an alternative random card sorting (RCS) approach - though this approach's susceptibility to range bias has not yet been formally tested. This study addressed this gap and showed, somewhat unexpectedly, that the RCS procedure was no less vulnerable to range bias than the PC method for eliciting both monetary values of health risk reductions and non-monetary estimates of death rates. Conclusions for future research initiatives are drawn.
Keywords: 330; Contingent valuation; elicitation format; risk reduction; willingness-to-pay